A retrospective case series on transvaginal repair of rectovaginal fistula performed by a urogynaecology operative team in Australia. (5th October 2021) - Thayalan, Krishanthy; Krause, Hannah; Goh, Judith
Abstract : Background: Rectovaginal fistula (RVF) is an abnormal epithelialised connection between the rectum and vagina. It is a common condition in limited resource settings and is caused almost exclusively by obstetric injury. In contrast, RVF is uncommonly seen in high resource settings. Aims: This study aims to review the aetiology and effectiveness of RVF management in the high resource setting, identifying predictors for repair success and long‐term outcomes. Materials and Methods: A retrospective case series study of patients who underwent transvaginal RVF repairs at two secondary healthcare facilities over a 14‐year period by one operative group. Results: A total of 41 patients underwent 46 surgical repairs. All patients presented with flatal and/or faecal incontinence and aetiology was identifiable in 78.0% ( n = 32). Obstetric cause was implicated in 26.8% ( n = 11) and other causes include 26.8% ( n = 11) from vaginal and abdominal surgery, 14.6% ( n = 6) from perianal abscess, 7.32% ( n = 3) as complications of Crohn's disease and 2.44% ( n = 1) as a complication of a cube pessary. Fistula was cured in 38 of 41 cases (92.7%) with a primary repair closure rate of 80.5% ( n = 33). Post‐operative symptoms were limited to flatal incontinence in 4.88% ( n = 2), faecal incontinence in 2.44% ( n = 1), and persistent perineal pain in 7.32% ( n = 3). The success of the surgical repair was not significantly impacted by fistula size, aetiology, presence of a stoma for diversion, history of prior repair, duration since RVF formation or repair technique. Conclusions: This review identifies aetiology for RVF in the high resource setting and highlights the role of earlier surgical repair to minimise patient morbidity with good success in closure and reduction of post‐operative symptoms.